Analisis Teknis dan Produktivitas Alat Tangkap Bubu Lipat di Kelurahan Pasar Bengkulu Kecamatan Sungai Serut Kota Bengkulu - Nur Lina Maratana Nabiu; Zamdial Zamdial; Albi Yosandri; Larzon Hanibal (Universitas Teuku Umar, 2023)
The Bengkulu City area with a large capture fishery activity is in the Sungai Serut District, precisely in the Pasar Bengkulu Village. Bubu Lipat is a fishing gear that is categorized into traps that are operated passively using bait. This research aims to analyze the technical and productivity of fishing gear used by fishermen in Pasar Bengkulu. It is expected to provide information, descriptions, and explanations about the development of traps to the government and related stakeholders for trap management in Pasar Bengkulu. The scope of the research data includes primary and secondary data, fishing gear construction, and catch productivity. Data collection was carried out through field observations, interviews, and documentation. The researchers conclude that the productivity of a trap per year is 1500 kilograms, and the productivity per trip is 30 kilograms. The catch of trap consists of two types, Keong Macan (Babylonia spirata) and Rajungan (Portunus pelagicus), and fishing vessels used by trap fishermen at the Pasar Bengkulu have two sizes, 1 and 2 GT with respective endurance of 10.5 PK and 26 PK. It is necessary to research the effectiveness of catching traps in Pasar Bengkulu to obtain more information regarding managing fishing gear in Pasar Bengkulu.